Diverse Activation Modes in the Hydroboration of Aldehydes and Ketones with Germanium, Tin, and Lead Lewis Pairs. Issue 1 (2nd December 2016) - Schneider, Julia; Sindlinger, Christian P.; Freitag, Sarah M.; Schubert, Hartmut; Wesemann, Lars
Abstract: Intramolecular germylene, stannylene, and plumbylene Lewis pairs were reacted with hexanal and yielded the cyclic addition products only with the germanium and tin reagents. In further reactivity studies, the hydroboration of aldehydes and ketones catalyzed by intramolecular germylene, stannylene, and plumbylene Lewis pairs was studied. In the case of the cyclic germylene Lewis pair, the product of the oxidative addition of pinacolborane at the germylene moiety was observed. According to stoichiometric as well as catalytic experiments, the intramolecular germylene Lewis pair acts as a catalyst in the hydroboration of aldehydes and ketones. The homologous stannylene Lewis pair forms a reactive tin hydride during the catalysis, which can also act as a catalyst in this transformation. Abstract : Divergent reactivity : Intramolecular germylene, stannylene, and plumbylene Lewis pairs were reacted with hexanal but only the germanium and tin reagents yielded the cyclic addition products. In further reactivity studies, the hydroboration of aldehydes and ketones catalyzed by these intramolecular Lewis pairs was investigated.